AB0902 Efficacy of tofacitinib by background methotrexate dose in patients with psoriatic arthritis: a post-hoc analysis of pooled data from 2 phase 3 trials. (12th June 2018) - Kivitz, A.J.; FitzGerald, O.; Nash, P.; Pang, S.; Azevedo, V.F.; Kudlacz, E.; Wang, C.; Graham, D.; Takiya, L.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of psoriatic arthritis (PsA). The efficacy of tofacitinib has been evaluated in 2 Phase 3 studies in patients (pts) with PsA. Objectives: To describe the efficacy of tofacitinib by background methotrexate (MTX) dose in pts with PsA. Methods: This post-hoc analysis utilised efficacy data pooled from 2 Phase 3, randomised, double-blind, placebo-controlled studies (OPAL Broaden [12 months; NCT01877668 ] and OPAL Beyond [6 months; NCT01882439 ]) in pts with a diagnosis (≥6 months) of active PsA (≥3 swollen and ≥3 tender joints). Pts in OPAL Broaden were tumour necrosis factor inhibitor (TNFi)-naïve and had an inadequate response (IR) to ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD). Pts in OPAL Beyond had an IR to ≥1 TNFi. Pts were randomised to tofacitinib 5 or 10 mg twice daily (BID), placebo or adalimumab 40 mg subcutaneous every 2 weeks (OPAL Broaden; adalimumab data not shown). All pts received a stable dose of 1 csDMARD (eg MTX, leflunomide or sulfasalazine) as background therapy. The maximum dose of MTX allowed per protocol was 20 mg/week. Efficacy outcomes for tofacitinib at Month 3 were evaluated by background MTX dose (≤15 vs>15 mg/week) and included: ACR20/50/70 response rates (≥20/50/70% improvement from baseline, respectively), Health Assessment Questionnaire-Disability Index (HAQ-DI) response rate (reduction from baseline ≥0.35 points) and mean change from baseline in HAQ-DI score. Analyses were based on the full analysis set for pts receiving MTX on Day 1; pts with missing data were considered as having a non-response for binary endpoints. No statistical testing was performed. Results: In total, data from 556 pts who received tofacitinib plus MTX only or placebo plus MTX only (tofacitinib 5 mg BID, n=186; tofacitinib 10 mg BID, n=178; placebo, n=192) were included in this analysis. Most pts were treated with background MTX at doses≤15 mg/week (n=371, 66.7%; mean [SD] dose, 12.6 [3.1] mg/week) vs >15 mg/week (n=185, 33.3%; mean [SD] dose, 19.8 [0.8] mg/week). Baseline demographics and disease characteristics were generally similar between arms in MTX dose groups (table 1). At Month 3, tofacitinib 5 and 10 mg BID were generally associated with numerically greater ACR and HAQ-DI response rates and greater changes from baseline in HAQ-DI score compared with placebo. The magnitude of tofacitinib effects on efficacy outcomes appeared broadly similar between background MTX dose groups (table 1). Missing values for ACR20/50/70 response rates and HAQ-DI response rate were considered as non-response to treatment LSM were calculated based on a mixed model for repeated measures without imputation for missing values The maximum permitted dose of MTX was 20 mg/week The analyses included all pts who received MTX as background therapy only on Day 1 in the FAS ACR, American College of Rheumatology; BID, twice daily; CRP, C-reactive protein; FAS, full analysis set; HAQ-DI, Health Assessment Questionnaire-Disability Index; LSM, least squares mean; MTX, methotrexate; n, number of pts with response; N, number of pts included in the analysis; N1, number of pts included in the HAQ-DI response analysis; N2, number of pts evaluable for change from baseline in HAQ-DI at Month 3; pts, patients; SD, standard deviation; SE, standard error Conclusions: The results of this pooled analysis suggest that the efficacy of tofacitinib in pts with PsA was greater than placebo and does not differ when evaluated by background MTX dose (≤15 vs>15 mg/week), although small pt numbers in some groups may limit the conclusions that can be made. These results are consistent with findings from similar analyses of tofacitinib in pts with rheumatoid arthritis. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by C Viegelmann of CMC and funded by Pfizer Inc. Disclosure of Interest: A. Kivitz Consultant for: AbbVie, Celgene, Genentech, Genzyme, Janssen, Merck, Novartis, Pfizer Inc, Sanofi and UCB, Speakers bureau: AbbVie, Celgene, Genentech, Genzyme, Janssen, Merck, Novartis, Pfizer Inc, Sanofi and UCB, O. FitzGerald Grant/research support from: AbbVie, BMS, Novartis, Pfizer Inc, Consultant for: Amgen, Celgene, Eli Lilly, Janssen, P. Nash Grant/research support from: AbbVie, BMS, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, BMS, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, BMS, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, S. Pang: None declared, V. Azevedo Grant/research support from: AbbVie, Eli Lilly, Genentech, GSK, Pfizer Inc, UCB, Consultant for: AbbVie, Merck-Serono, Novartis, Pfizer Inc, Speakers bureau: AbbVie, Janssen, Merck-Serono, Novartis, Pfizer Inc, Sanofi, E. Kudlacz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Takiya Shareholder of: Pfizer Inc, Employee of: Pfizer Inc